Long-Term Effects of Saline Boluses in Very Preterm Infants (VPI). (1st June 2016) - Aslam, A; Vincer, M; Allen, A; Imanullah, S; Connell, C O'
Abstract: BACKGROUND: Normal saline bolus is commonly used in clinical practice for treating hypotension in term and preterm neonates during resuscitation in early life despite the paucity of high quality evidence supporting this practice. OBJECTIVES: To determine the effects of normal saline boluses given within seven days of birth in VPI less than 31 weeks at 18 to 36 of months corrected age. DESIGN/METHODS: This is a retrospective population-based cohort analysis of the use of saline boluses from January 2006 to December 2010, of VPI from Halifax County. The outcomes at 18-36 months corrected age were extracted from the Perinatal Follow-Up Program (PFUP) database. This program is dedicated to the care and monitoring of infants who were VPI, very low birth weight or those who had brain injury at birth. It includes the evaluation of long-term developmental outcomes, multidisci-plinary services including rehabilitation, dietetics and social services. Primary Outcome: To assess the incidence of death, cerebral palsy, language, cognitive delay, hearing impairment requiring the amplification, or bilateral blindness at the corrected 18-36 months of VPI who did or did not receive normal saline boluses. Secondary Outcome: To assess patent ductus arteriosus(PDA), bronchopulmonary dysplasia (BPD), intraventricular hemorrhage (IVH), periventricular leucomalacia, necrotizing enterocolitis (NEC) and retinopathy of prematurity (ROP) between VPI who did or did not receive normal saline boluses. Inclusion criteria: VPI from Halifax County admitted to the NICU at the IWK Health Centre, Halifax, Nova Scotia, Canada between January 2006 to December 2010. Exclusion criteria: Infants with major congenital anomalies and who were not offered resuscitation in the delivery room and expected to die. RESULTS: The regression analysis indicated that there was no difference in terms of death or disability between those who received saline bolus 15 (53.6%) versus those who did not receive saline boluses 45 (34.6%), [OR 2.17 (0.94, 5.05) p = 0.07]. Although univariate comparisons between the two groups showed significant differences in rates of PDA, severe IVH, NEC, cystic PVL, BPD and ROP, but after controlling for the influences of birth weight, APGAR score at 1 minute, admission BP and hemoglobin, bolus treatment was not significantly related to any of these outcomes CONCLUSION: In the current study no significant difference was found between the two groups in terms of long term neurodevelopmental outcomes and short term outcomes were significantly different only in univari-ate comparisons. Given the limitations of this retrospective study, a randomized controlled trial to evaluate the effects of normal saline boluses use during early life on neurodevelopment outcomes is warrented.